Changes in PGE2 signaling after submandibulectomy alter post–tooth extraction socket healing - Mohn, Claudia Ester (2018)
Saliva is very important to oral health, and a salivary deficit has been shown to bring serious problems to oral health. There is scant information about the mechanisms through which salivary glands participate in post–tooth extraction socket healing. Therefore, the aim of the present study was to investigate the effect of submandibulectomy (SMx), consisting of the ablation of submandibular and sublingual glands (SMG and SLG, respectively), on PGE2 signaling and other bone regulatory molecules, such as OPG and RANKL, involved in tooth extraction socket healing. Male Wistar rats, 70 g body weight, were assigned to an experimental (subjected to SMx) or a control group (sham operated). One week later, the animals in both groups underwent bilateral extraction of the first mandibular molars. The effect of SMx on different stages of socket healing after tooth extraction (7, 14, and 30 days) was studied by evaluating some parameters of inflammation, including PGE2 and its receptors, and of bone metabolism, as well as by performing bone biomechanical studies. SMx increased TNFα and PGE2 content as well as cyclooxygenase-II (COX-II) expression in tooth socket tissue at almost all the studied time points. SMx also had an effect on mRNA expression of PGE2 receptors at the different time points, but did not significantly alter osteoprotegerin (OPG) and RANKL mRNA expression at any of the studied time points. In addition, an increase in bone mass density was observed in SMx rats compared with matched controls, and the structural and mechanical bone properties of the mandibular socket bone were also affected by SMx. Our results suggest that the SMG/SLG complex regulates cellular activation and differentiation by modulating the production of molecules intervening in tooth extraction socket repair, including the PGE2 signaling system, which would therefore account for the higher density and resistance of the newly formed bone in SMx rat.